2004
DOI: 10.1179/146531204225026679
|View full text |Cite
|
Sign up to set email alerts
|

Current Products and Practices OrthoCAD™: digital models for a digital era

Abstract: This article describes the use of OrthoCAD--a digital study model capture, assessment and storage system. It is estimated that approximately 10% of orthodontists in USA and Canada now utilize digital study models, and improving technology is making it increasingly popular worldwide. The technology behind digital study models is briefly reviewed. The OrthoCAD system is described, and the advantages and disadvantages of using digital study models are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 4 publications
0
54
0
5
Order By: Relevance
“…9 However reliable and accurate these measurements may be, they still involve the actual process of taking impressions and subsequent scan of these impressions, which can take up to 10 days to complete. 10 Most current imaging techniques, such as CBCT, could potentially eliminate the time-consuming and often uncomfortable process of taking impressions; however, newer methods must also be examined for safety, reliability, and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…9 However reliable and accurate these measurements may be, they still involve the actual process of taking impressions and subsequent scan of these impressions, which can take up to 10 days to complete. 10 Most current imaging techniques, such as CBCT, could potentially eliminate the time-consuming and often uncomfortable process of taking impressions; however, newer methods must also be examined for safety, reliability, and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, recent advances in 3D analysis have been used for accurate assessment of positional changes after tooth movement. 21 Stable structures, including the palatal surface and nonmoved teeth, facilitate accurate superimposition at different treatment time intervals. However, 3D analysis of tooth movement following intrusion of a single supraerupted molar using a mini-implant has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Digital models have a number of advantages in terms of storage, retrieval, diagnostic versatility, transferability, and durability. 10,11 Numerous studies have shown that 3D digital models can be used for model analysis and diagnosis, 10,[12][13][14][15][16] treatment planning, 8,17 design and manufacture of orthodontic appliances, [18][19][20] and evaluation of tooth movement. [21][22][23][24] To date, however, studies of the reliability of computed superimposition of 3D digital models to assess the outcomes of orthodontic treatments have been limited.…”
Section: Introductionmentioning
confidence: 99%